CONTENTS OF SEDIMENT ORGANIC AND MACROZOOBENTOS INGREDIENTS IN SUNGAI PAKNINGBENGKALIS DISTRICT RIAU PROVINCE - Uju Doi Sibarani; Yusni Ikhwan Siregar; Musrifin Galib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT           This research was conducted in January 2019, the sample was collected from the  coastal waters of Sungai Pakning, Bengkalis Regency, Riau Province. This study aims to analysis content of organic sediments and abundance of macrozoobenthos, then the relationship between the content of organic matter and the abundance of macrozoobenthos in the waters of the Sungai Pakning. The method used in the research is the survey method. The range of organic matter in the waters of the Sungai Pakning is 6,73%-12,76% and the abundance of the average macrozoobenthos is 11,85 ind/m2-17,78 ind/m2 with the dominant species being Anadara granosa. The influence of organic matter content on macrozoobenthos abundance has a coefficient determination (R2) of 0,406 which means that the influence of organic matter in the waters of the Sungai Pakning is 40,60% while 59,40% is influenced by other factors. This is because the mangrove vegetation contributes greatly to organic matter.Keywords: Sungai Pakning, Sediment Organic Matter, Macrozoobenthos, Anadara granosa, Mangrove vegetation.